"Rotten Row is Rotten to the Core": the material and sensory politics of Harare's magistrates courts after 2000 - Verheul, SJ (American Anthropological Association, 2020)
In this article, I ask how state power and authority were established and critiqued through the performative, material and sensory characteristics of Harare’s Criminal Magistrates’ Courts in Zimbabwe. Drawing on courtroom observations and interviews conducted with human rights lawyers and their clients between 2010 and 2018, I show how Zimbabwe’s deteriorating political and economic situation after 2000 caused a decline of the material conditions in court. Lawyers and their clients played on this decline to emphasize how the state failed to display its authority. Simultaneously, these material conditions highlighted the ruling party, ZANU-PF’s, preoccupation with law’s coercive rather than legitimating utility. In order to examine the ways in which court proceedings impose and challenge the authority of the law, and of the state, however, a focus on material attributes does not suffice. The sensory dimensions of courtrooms also require attention. By engaging with not only the visual and auditory, but also, and importantly, the olfactory, reminders of the horrific conditions in police detention and prison within the courtroom, lawyers and their clients reasserted and questioned not the authority of law, but the control certain state actors exerted on and over the bodies and emotions of Zimbabwean citizens within legal spaces.